Fabrication of magnetic bimetallic Fe3O4@Au–Pd hybrid nanoparticles with recyclable and efficient catalytic properties. Issue 60 (8th June 2016) - Xia, Qingdong; Fu, Shanshan; Ren, Guojuan; Chai, Fang; Jiang, Jingjie; Qu, Fengyu
Abstract : View of the preparation process and evaluation of the catalytic activity of Fe3 O4 @Pd and Fe3 O4 @Au–Pd NPs. Abstract : Bimetallic nanostructures show exciting potential as materials for effective catalysis. Magnetically recoverable bimetallic nanoparticles are promising catalysts for chemical reactions. Here, Fe3 O4 @Pd and Fe3 O4 @Au–Pd hybrid nanoparticles were synthesized and used as catalysts. The morphology, composition, and structure of the Fe3 O4 @Pd and Fe3 O4 @Au–Pd hybrid nanoparticles were fully characterized by scanning and transmission electron microscopy, energy dispersive spectroscopy, high angle annular dark-field scanning TEM, X-ray powder diffraction, X-ray photoelectron spectroscopy, etc. The Fe3 O4 @Pd and Fe3 O4 @Au–Pd nanoparticles show excellent catalytic activity towards the reduction of nitrophenols and potassium hexacyanoferrate(iii ). In addition, the magnetic bimetallic heterogeneous nanoparticles can be easily recycled, showing good reusability; conversion higher than 99% was achieved after 6 cycles.